Biomarkers, Clinical Course, and Individual Needs in COPD Patients in Primary Care: The Study Protocol of the Stockholm COPD Inflammation Cohort (SCOPIC) - Lundh L; Larsson K; Lindén A; Montgomery S; Palmberg L; Sandelowsky H (International Journal of COPD, 2022)
Lena Lundh,1,2 Kjell Larsson,3 Anders Lindén,4,5 Scott Montgomery,6– 8 Lena Palmberg,3 Hanna Sandelowsky1,2,7 1Academic Primary Health Care Centre, Stockholm County Council, Stockholm, Sweden; 2Division of Family Medicine and Primary Care, Department of Neurobiology, Care Sciences and Society, Karolinska Institutet, Huddinge, Sweden; 3Division of Integrative Toxicology, Institute of Environmental Medicine, Karolinska Institutet, Stockholm, Sweden; 4Division for Lung and Airway Research, Institute of Environmental Medicine, Karolinska Institutet, Stockholm, Sweden; 5Karolinska Severe COPD Center, Department of Respiratory Medicine and Allergy, Karolinska University Hospital Solna, Stockholm, Sweden; 6Clinical Epidemiology and Biostatistics, School of Medical Sciences, Örebro University, Örebro, Sweden; 7Division of Clinical Epidemiology, Department of Medicine Solna, Karolinska Institutet, Stockholm, Sweden; 8Department of Epidemiology and Public Health, University College London, London, UKCorrespondence: Hanna Sandelowsky, Karolinska Institutet, Department of Medicine, Division of Clinical Epidemiology, Stockholm, SE-171 76, Sweden, Tel +46738902565, Email hanna.sandelowsky@ki.seBackground: To facilitate effective personalized medicine, primary health care needs better methods of assessing and monitoring chronic obstructive pulmonary disease (COPD).Aim: This cohort study aims to investigate how biomarkers relate to clinical characteristics and COPD patients’ subjective needs over time.Methods: Patients (n=750) in different COPD severity according to the GOLD criteria and age- and sex-matched controls (n=750) will be recruited over a period of 5 years from 15 primary health care centers in Region Stockholm, Sweden, and followed for 10 years in the first instance. Data on patients’ subjective needs will be collected via telephone/email, data on clinical/physiological variables (eg, symptoms, exacerbations, comorbidities, medications, smoking habits, lung function) from existing databases that are based on medical records, and data on biomarkers via repeated blood sampling. Quantitative and qualitative methods will be used. Initial results are expected after 2 years (feasibility test), and a larger body of evidence after 5 years.Discussion: The study is expected to provide definitive and clinically useful scientific evidence about how biomarkers relate to clinical variables and patients’ subjective needs. This new evidence will facilitate accurate, and personalized COPD management by the use of valid biomarkers. It will provide useful tools for primary care professionals and may facilitate optimal self-management.Keywords: airway inflammation, COPD, biomarkers, cohort, patients’ needs, personalized medicine, primary care